Mount Lu Revisited: Buddhism in the Life and Writings of Su Shih. Beata Grant. - Tarocco, Francesca (Buddhist Studies Review, 2003)
Mount Lu Revisited: Buddhism in the Life and Writings of Su Shih. Beata Grant. University of Hawai’i Press, Honolulu 1994. 249 pp. $36.00. ISBN 0-8248-1625-0.